Mobile phones in daily life - La Rosa, Amaro (2015)
The article attempts an approximation to behavioral and sociocultural transformations produced in contemporary daily life, derived from the massive use of mobile phones. Part of the rapid development of mobile technologies and growth of its coverage that in diverse countries exceeds number of inhabitants, which it has converted to these resources into objects of privileged consumption with a high rate of technological obsolescence. It describes how in relation with the use of mobile phones have changed, in practical terms the concept of public and private spaces.